Hegel on Human Ways of Considering Nature - Marco Palombelli (Ethics in Progress)
In this article I aim to show the limits of certain "ways of considering" nature, as well as the intrinsic contradictions in their modus operandi, following Hegel's analysis in the Introductions to the Encyclopaedic Naturphilosophie and the Berlin Lectures on the Philosophy of Nature. After framing the problem within the broader theme - already explored in Jena - of the relationship between nature and spirit, I will show that both the practical and the theoretical, insofar as they are founded in an original separation between man and nature, result in a subjection of the natural being to man. In order for this to be redeemed from one-sided conduct towards it, it is necessary to access through living intuition a philosophical consideration – both of the living being and of nature as a whole –, the activity of which Hegel understands as a rediscovery of the rationality of nature and its "liberation”.